Formation of professional sports culture of the personality of cadets of educational organizations of the federal penitentiary service of russia in the aspect of methodological approaches - Zvyagintsev M.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to theoretically substantiate the conceptual apparatus and methodological foundations of the formation of professional sports culture of the personality of cadets of educational organizations of the Federal Penitentiary Service of Russia. Methodology and organization of the study. The work applies a theoretical analysis of scientific works of various authors, extrapolates and formulates the concept of professional sports culture of personality of cadets. Results and conclusions. The concept of professional sports culture of the individual is clarified, a comparative analysis is carried out with such concepts as: physical culture of the individual, applied physical training, sports culture of the individual. Conceptual provisions for the formation of a professional sports culture of an individual have been developed.